Teachers’ and Students’ Understanding and Perception of the National Assessment in Indonesian Primary Schools: Implications for Learning and Classroom Assessment - Driana, Elin; Ningsih, Annisa Maulidyah; Ernawati, Ernawati; Setiadi, Hari (Universitas Pendidikan Indonesia, 2025)
National assessments are essential tools for evaluating educational quality worldwide. In Indonesia, the National Assessment (NA) was introduced to assess literacy, numeracy, character, and the learning environment without direct consequences for individual students. This study was conducted to explore teachers' and students' understanding and perceptions of NA, as well as its implications for classroom learning and assessment. A qualitative method with phenomenological approach was used, involving semi-structured interviews with 11 teachers and 21 fifth-grade students from six public schools in South Jakarta. The findings revealed that most teachers had a basic understanding of NA, with varied interpretations of its purpose and components. Teachers viewed NA as necessary for improving education quality but emphasized the need for better infrastructure and pedagogical support. Students, on the other hand, perceived NA as a low-stakes test with limited impact on their learning. Despite these differing views, the implementation of NA motivated improvements in literacy and numeracy, and increased the use of technology in teaching. However, challenges such as digital literacy gaps and limited device access were noted. The study contributes valuable insights into the perceptions of teachers and students, highlighting the need for infrastructure, training, and the effective use of assessment data to improve educational quality.